Clinical monitoring and management of complications related to chelation therapy in patients with β-thalassemia. Issue 2 (1st February 2016) - Saliba, Antoine N.; El Rassi, Fuad; Taher, Ali T.
ABSTRACT: Iron chelating agents – deferoxamine (DFO), deferiprone (DFP), and deferasirox (DFX) – are used to treat chronic iron overload in patients with β-thalassemia in an attempt to reduce morbidity and mortality related to siderosis. Each of the approved iron chelating agents has its own advantages over the others and also has its own risks, whether related to over-chelation or not. In this review, we briefly discuss the methods to monitor the efficacy of iron chelation therapy (ICT) and the evidence behind the use of each iron chelating agent. We also portray the risks and complications associated with each iron chelating agent and recommend strategies to manage adverse events.